Factors Determining the Performance of the Indonesian Agricultural Sector in the Era of Climate Change - Qiki Qilang Syachbudy; Yusman Syaukat; Noer Azam Achsani; Nia Kurniawati Hidayat (Jurnal Ilmu Pertanian Indonesia, 2025)
The agricultural sector plays a crucial role in Indonesia, serving as both a provider of food and a key driver of economic growth. This study aims to analyze the factors influencing Indonesia’s agricultural sector from 1981 to 2021, focusing on agricultural production and its economic value. Climate change has emerged as a critical issue affecting agriculture, with greenhouse gas emissions serving as proxies for measuring its impact. This study employs the Autoregressive Distributed Lag (ARDL) model to examine both short- and long-term relationships. The findings indicate that, in the long run, agricultural land area and economic growth significantly affect the agricultural sector. In the short term, agricultural land area, economic growth, and fertilizer usage are the key factors. However, climate change did not have a significant negative impact on agricultural decline. In contrast, fertilizer usage was positively correlated with agricultural production. These findings highlight the essential role of government policy in fostering agricultural sector development in Indonesia. Strategic initiatives should focus on ensuring an adequate fertilizer supply, expanding agricultural land, and promoting key economic sectors that drive growth and support agricultural sustainability. Keywords: agricultural sector, ARDL model, climate change, Indonesia